Measuring and Replicating the 1–20 μm Energy Distributions of the Coldest Brown Dwarfs: Rotating, Turbulent, and Nonadiabatic Atmospheres - Leggett, S. K.; Tremblin, Pascal; Phillips, Mark W.; Dupuy, Trent J.; Marley, Mark; Morley, Caroline; Schneider, Adam; Caselden, Dan; Guillaume, Colin; Logsdon, Sarah E. (The Astrophysical journal, 2021)
Cold, low-mass, field brown dwarfs are important for constraining the terminus of the stellar mass function, and also for optimizing atmospheric studies of exoplanets. In 2020 new model grids for such objects were made available: Sonora-Bobcat and ATMO 2020. Also, new candidate cold brown dwarfs were announced, and new spectroscopic observations at λ ≈ 4.8 μ m were published. In this paper we present new infrared photometry for some of the coldest brown dwarfs, and put the new data and models together to explore the properties of these objects. We reconfirm the importance of mixing in these atmospheres, which leads to CO and NH 3 abundances that differ by orders of magnitude from chemical equilibrium values. We also demonstrate that the new models retain the known factor ≳3 discrepancy with observations at 2 ≲ λ μ m ≲ 4, for brown dwarfs cooler than 600 K. We show that the entire 1 ≲ λ μ m ≲ 20 energy distribution of six brown dwarfs with 260 ≤ T eff K ≤ 475 can be well reproduced, for the first time, by model atmospheres which include disequilibrium chemistry as well as a photospheric temperature gradient which deviates from the standard radiative/convective equilibrium value. This change to the pressure–temperature profile is not unexpected for rotating and turbulent atmospheres that are subject to diabatic processes. A limited grid of modified-adiabat model colors is generated, and used to estimate temperatures and metallicities for the currently known Y dwarfs. A compilation of the photometric data used here is given in Appendix C.